Effectiveness Of Prenatal Massage On Reducing Physical Complaints In Pregnant Women Trimester III - Marta Imelda Sianturi (Science Midwifery, 2021)
Prenatal massage is one way to bring out wellness for body and mind in third trimester pregnant women, which can be overcome to overcome the physical Pe al problems they experience. The formulation of the problem in this study is the physical complaints experienced by pregnant women in the form of cramps in the legs, edema in the legs, back pain, difficulty sleeping can be resolved with prenatal massage and aims to determine the effectiveness of prenatal massage on physical complaints in third trimester pregnant women at the clinic Pera. The type of research is Quasi Experiment with Non Equivalent Control Group approach. The research sample was 32 pregnant women with third trimester, namely 16 people as the intervention group, 16 people as controls taken with consecutive sampling technique. Univariate analysis, Wilcoxon test and Mann Whitney test. The results of the mean value between the pre-test and post-test measurements of the control group was -0.25; (p=0.417>=0.05). The result of the mean value between the pre-test and post-t est measurements of the intervention group was 3.5; (p=0,000 <α=0,05). And the results of the difference in the average value of physical complaints in the control group and the intervention group are 3.75; (p = 0.000 < = 0.05, there is a significant difference in the average value of respondents' physical complaints between the control group and the intervention group.) So the key is that prenatal massage is effective in reducing physical complaints of pregnant women in the third trimester. Physical complaints that are often experienced by pregnant women can be reduced.